EFEKTIVITAS ANGKUR EPOKSI TERHADAP KEKANGAN EKSTERNAL BALOK BETON BERTULANG DENGAN PERKUATAN CFRP - Dinar Gumilang Jati; Junaedi Utomo; Felix Adi Tanudjaja; Han Ay Lie (Jurnal Teknik Sipil, 2023)
Externally Bonded Carbon Fiber Reinforced Polymer (EB-CFRP) with U-wrap is one of the alternative external strengthening of modern reinforced concrete beams, which has been proven effective in significantly increasing flexural and deformation capacities. Although quite effective in increasing the structural capacity, external reinforcement needs to be studied further about its failure behavior, the avoided failure is called debonding, an interface bond failure between the FRP composite material and the concrete material. Epoxy has a fairly high material resistance, but its use as a reinforcing composite bonding material needs further investigation. Adding epoxy anchors at the ends of CFRP can mobilize the tensile strength in CFRP, eliminating or delaying debonding failure. Epoxy anchors (epoxy-filled grooves) are expected to be effective and flexible for application to various forms of components of reinforced concrete structures that have been reinforced with EB-CFRP. Currently, there are no standards and guidelines for applying FRP anchors. However, research has been conducted on the failure pattern of FRP anchors with U-style wrapping which can avoid debonding so that failure with FRP rupture can be achieved. This study examines the effectiveness of epoxy anchorage in improving the external strengthening of reinforced concrete beams with EB-CFRP reinforcement. The behavior of epoxy anchors in reinforced concrete beams with EB-CFRP will be investigated through experimental tests.